Transformasi Kuttau Lampung dari Beladiri menjadi Seni Pertunjukan Tari Pedang - Indra Bulan (Universitas Gadjah Mada, 2017)
Transformation of kuttau Lampung from martial art become Tari Pedang performance research, has been done at Sukadana Village in East Lampung Regency. To examine both kuttau and Tari Pedang in the forms of martial art and performance contexts. The objective of this reaserch is to show the transformation form and martial art value of kuttau become Tari Pedang performance. Otherwise to show the transformation agent factor that happened in kuttau. The research of art examine, has been done byparticipant observation, supported by some theory. The approach used in this research is performance studies. To analysis the form of kuttau in martial art context are used the text theory that is discuss as text and context. Continued by analysis of transformation form used adaptation and appropriation theory, that is also discuss as text and context. In general, the result of this research are both kuttau and Tari Pedang in the forms ofmartial art and performance contexts.the basic element that distinguish between kuttau and Tari Pedang are the change of martial art aesthetic become performance aesthetic. Otherwise Tari Pedang is representation of kuttau in theatrical mimicry form, even the movements, costums, and other elements are adaptation, but only imitation without scenario. Tari Pedang is the result of appropriation process, although the text of Tari Pedang was adaptation from kuttau. But, the context of Tari Pedang is very different from the origin, so we can assume that the result of appropriation process are new product that following the society supporter pretentions.